The role of financial process re-engineering in alleviating the pressures of in commercial banks of Al-Muthanna - Aseal Kareem, Dhurgham; Obaid, Huda Abdul Hadi; Taha, Hiba Yousif (South Asian Journal of Social Sciences and Humanities, 2024)
The study aims to clarify and apply the re-engineering of financial operations to reduce the pressures of banking work among workers in commercial banks. The researchers used the questionnaire as a main tool for collecting data by selecting a random sample of (250) respondents and testing the research hypotheses using descriptive and inferential statistics methods, in addition to using personal interviews and field observations as auxiliary tools in collecting data. The statistical programs (SPSS 16.16) were used. V.25; Excel V). The results of the statistical analysis showed that there is a singnificant effect and correlation between the re-engineering of financial operations and the pressures of banking work. Also, the re-engineering of financial operations contributes to increasing the effective impact in order to reach the stage of contributing to reducing. Its recommended to difficulties in some work must be alleviated in order to reduce the pressure on employees.